NOMS 2018 - 2018 IEEE/IFIP Network Operations and Management Symposium 2018
DOI: 10.1109/noms.2018.8406217
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic video bitrate adaptation for WebRTC-based remote teaching applications

Abstract: Abstract-Remote teaching applications are common nowadays. Very often, these applications resemble video-on-demand streaming platforms rather than real virtual classrooms, where a group of students (the receivers) can remotely attend a live lecture held by a lecturer (the sender). To better support this live scenario, Real-Time Communication (RTC) solutions can be used. WebRTC is an open-source project for real-time browserbased conferencing, developed with a peer-to-peer architecture in mind. To use WebRTC, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…and therefore maximize the received bitrate. A preliminary evaluation of the proposed framework has been presented in previous work [11], where we showed that the dynamic bitrate recomputation results in 15% higher video rate at the receivers compared to a static, fixed association of the encoding bitrates.…”
Section: Related Workmentioning
confidence: 88%
“…and therefore maximize the received bitrate. A preliminary evaluation of the proposed framework has been presented in previous work [11], where we showed that the dynamic bitrate recomputation results in 15% higher video rate at the receivers compared to a static, fixed association of the encoding bitrates.…”
Section: Related Workmentioning
confidence: 88%
“…Bitrate adaptation methods for WebRTC have been studied [10]- [12], [14], [15]. GCC [10], [11], which is one of the well-known methods, controls bitrate on the basis of jitter and packet loss rate.…”
Section: Bitrate Control Algorithmmentioning
confidence: 99%
“…Wang et al proposed a scalable video coding (SVC) layer bitrate selection algorithm for multiparty interactive live video streaming to maximize the total quality of the receiver on the basis of the sender's uplink throughput, receiver's downlink throughput, and buffer occupancy [12]. Petrangeli et al proposed a video bitrate control method for WebRTC-based remote teaching applications that maximizes the video bitrate transmitted to the receiver, taking into account the available bandwidth of the receiver [15]. This method can control the video bitrate in response to bandwidth fluctuations.…”
Section: Bitrate Control Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Their method introduces a conference controller and instructed the sender to encode fewer bitrate patterns than the number of receivers to reduce the encoding cost. In addition, it was found that the bandwidth could be efficiently utilized by varying the encoding bitrates in accordance with the bandwidth of the receiver [7]. These methods are expected to reduce server infrastructure costs, but that is not expected to reduce the transferred data volume.…”
Section: Introductionmentioning
confidence: 99%